Calcium Microdomain Formation at the Perisynaptic Cradle Due to NCX Reversal: A Computational Study - Wade, John Joseph; Breslin, Kevin; Wong-Lin, KongFatt; Harkin, Jim; Flanagan, Bronac; Van Zalinge, Harm; Hall, Steve; Dallas, Mark; Bithell, Angela; Verkhratsky, Alexei; McDaid, Liam (Frontiers in Cellular Neuroscience, 2019)
It has recently been proposed using a multi-compartmental mathematical model that negatively fixed charged membrane-associated sites constrain the flow of cations in perisynaptic astroglial processes. This restricted movement of ions between the perisynaptic cradle (PsC), principal astroglial processes and the astrocyte soma gives rise to potassium (K+) and sodium (Na+) microdomains at the PsC. The present paper extends the above model to demonstrate that the formation of an Na+ microdomain can reverse the Na+/Ca2+ exchanger (NCX) thus providing an additional source of calcium (Ca2+) at the PsC. Results presented clearly show that reversal of the Na+/Ca2+ exchanger is instigated by a glutamate transporter coupled increase in concentration of cytoplasmic [Na+]i at the PsC, which and instigates Ca2+ influx through the NCX. As the flow of Ca2+ along the astrocyte process and away from the PsC is also constrained by Ca2+ binding proteins, then a Ca2+ microdomain forms at the PsC. The paper also serves to demonstrate that the EAAT, NKA, and NCX represent the minimal requirement necessary and sufficient for the development of a Ca2+ microdomain and that these mechanisms directly link neuronal activity and glutamate release to the formation of localized Na+ and Ca2+ microdomains signals at the PsC. This local source of Ca2+ can provide a previously underexplored form of astroglial Ca2+ signaling.